Advanced Diabetic Nephropathy with Nephrotic Range Proteinuria: A Pilot Study of the Long-Term Efficacy of Subcutaneous ACTH Gel on Proteinuria, Progression of CKD, and Urinary Levels of VEGF and MCP-1 - Tumlin, J. A. (Hindawi Publishing Corporation, 2013)
Background and Objective. Adrenocorticotropic hormone (ACTH) is able to reduce proteinuria in nondiabetic glomerulopathies through activation of melanocortin receptors (MCR) expressed in the podocyte. To determine the efficacy of ACTH, we conducted a randomized, open-label pilot trial of ACTH gel in patients with advanced diabetic nephropathy. Study Design. Twenty-three (23) patients with diabetic nephropathy were randomized to daily subcutaneous (SQ) injections of 16 or 32 units of ACTH gel for six months. Outcome. The primary endpoint was the percentage of patients achieving a complete remission (<300 mg/24 hours) within 6 months. Exploratory endpoints included the percentage of partial (50% reduction) remissions, changes in Cr, and urinary cytokine markers. Results. After 6 months of ACTH gel therapy, 8 of 14 (57%) patients achieved a complete (n = 1) or partial (n = 7) remission. In the low-dose ACTH gel group (16 units), urinary protein fell from 6709 + 953 to 2224 + 489 mg/24 hrs (P < 0.001). In contrast, 2 of 6 patients in the 32-unit group achieved partial remission, but aggregate proteinuria (5324 + 751 to 5154 + 853 mg/24 hours) did not change. Urinary VEGF increased from 388 to 1346 pg/mg urinary creatinine (P < 0.02) in the low-dose group but remained unchanged in the high-dose group. Conclusion. ACTH gel stabilizes renal function and reduces urinary protein for up to 6 months after treatment. The ClinTrials.gov identifier is NCT01028287.